La inclusión sociolaboral de la población reclusa de Galicia, Espa\~na: principales obstáculos y propuestas para su superación - María Barreiro-Gen (Atlantic Review of Economics, 2012)
– The current economic crisis makes harder to get a job. Also, certain groups have more difficult due to other factors such as social mistrust. It's the case of people who leave or are about to leave a prison. Therefore, we analyzed the employability of prisoners serving grade 3 in Galicia. Our paper shows a qualitative analysis based on face to face interviews with prisoners and those at grade third whom managed to get a job. The objective was to analyse the kind of the jobs obtained, and to analyse the most significant difficulties to get their target. Results achieved are a mix, depending on individual characteristics of each one of ex-prisoners, but we have found that the availability of a strong social and family network is a key point for the successful job search
Keywords: J71; J78; K10; 330